Clinical features and mortality predictors of older hospitalized patients with severe COVID-19 in Lima, Per? - Romero-Ortuno, Roman (My University, 2022)
Background and aims. The objective of our study was to describe the clinical features of severe COVID-19 in older (compared to younger) hospitalized patients in a tertiary care centre in Lima, Perú. Methods. A retrospective observational study was conducted that included patients hospitalized for severe COVID-19 between March and May 2020. The clinical features of the older group (age ≥ 60 years) were compared with those of younger patients (age < 60 years). A classification and regression tree (CRT) was computed to evaluate and visualize the main predictors of mortality in the total sample. Results. The study included 339 patients, 213 in the older and 126 in the younger group. Mortality was higher in the older group, 76.5% vs. 42.1% (p < 0.001). Within the older group, factors associated with higher mortality were older age (p = 0.006), hypertension (p = 0.039) and obesity (p = 0.034). The older group had higher D-Dimer (p = 0.044), C-reactive protein (CRP) (p = 0.031) and total bilirubin (p = 0.007); and lower lymphocyte count (p = 0.003), albumin (p < 0.001) and Alanine aminotransferase (ALT) (p = 0.003). In the older group, CRT showed that the best predictor of mortality was the chest Computed Tomography Total Severity Score, with those with a score over 12 having 85.2% mortality. Conclusions. Mortality in patients hospitalized with severe COVID-19 was high, especially in older patients. In the latter, mortality was best predicted by an objective radiological marker of chest disease.
PUBLISHED
Keywords: SARS-CoV-2; COVID-19; mortality; older age; risk factors; Ageing; Immunology, Inflammation & Infection; International Development; Age-related disability; Health; Third age/ageing